Long-term evaluation of the antimicrobial susceptibility and microbial profile of subgingival biofilms in individuals with aggressive periodontitis - Lourenço, Talita Gomes Baêta (Braz J Microbiol, 2015)
This study evaluates the antimicrobial susceptibility and composition of subgingival biofilms in generalized aggressive periodontitis (GAP) patients treated using mechanical/antimicrobial therapies, including chlorhexidine (CHX), amoxicillin (AMX) and metronidazole (MET). GAP patients allocated to the placebo (C, n = 15) or test group (T, n = 16) received full-mouth disinfection with CHX, scaling and root planning, and systemic AMX (500 mg)/MET (250 mg) or placebos. Subgingival plaque samples were obtained at baseline, 3, 6, 9 and 12 months post-therapy from 3–4 periodontal pockets, and the samples were pooled and cultivated under anaerobic conditions. The minimum inhibitory concentrations (MICs) of AMX, MET and CHX were assessed using the microdilution method. Bacterial species present in the cultivated biofilm were identified by checkerboard DNA-DNA hybridization. At baseline, no differences in the MICs between groups were observed for the 3 antimicrobials. In the T group, significant increases in the MICs of CHX (p < 0.05) and AMX (p < 0.01) were detected during the first 3 months; however, the MIC of MET decreased at 12 months (p < 0.05). For several species, the MICs significantly changed over time in both groups, i.e., Streptococci MICs tended to increase, while for several periodontal pathogens, the MICs diminished. A transitory increase in the MIC of the subgingival biofilm to AMX and CHX was observed in GAP patients treated using enhanced mechanical therapy with topical CHX and systemic AMX/MET. Both protocols presented limited effects on the cultivable subgingival microbiota.